ACT001 Inhibits TLR4 Signaling by Targeting Co-Receptor MD2 and Attenuates Neuropathic Pain - Zhang, Tianshu; Lin, Cong; Wu, Siru; Jin, Sha; Li, Xiaodong; Peng, Yinghua; Wang, Xiaohui (Frontiers in Immunology, 2022)
Neuropathic pain is a common and challenging neurological disease, which renders an unmet need for safe and effective new therapies. Toll-like receptor 4 (TLR4) expressed on immune cells in the central nervous system arises as a novel target for treating neuropathic pain. In this study, ACT001, an orphan drug currently in clinical trials for the treatment of glioblastoma, was identified as a TLR4 antagonist. In vitro quenching titrations of intrinsic protein fluorescence and saturation transfer difference (STD)-NMR showed the direct binding of ACT001 to TLR4 co-receptor MD2. Cellular thermal shift assay (CETSA) showed that ACT001 binding affected the MD2 stability, which implies that MD2 is the endogenous target of ACT001. In silico simulations that ACT001 binding decreased the percentage of hydrophobic area in the buried solvent-accessible surface areas (SASA) of MD2 and rendered most regions of MD2 to be more flexible, which is consistent with experimental data that ACT001 binding decreased MD2 stability. In keeping with targeting MD2, ACT001 was found to retrain the formation of TLR4/MD2/MyD88 complex and the activation of TLR4 signaling axes of NF-κB and MAPKs, therefore blocking LPS-induced TLR4 signaling downstream pro-inflammatory factors NO, IL-6, TNF-α, and IL-1β. Furthermore, systemic administration of ACT001 attenuated allodynia induced by peripheral nerve injury and activation of microglia and astrocyte in vivo. Given the well-established role of neuroinflammation in neuropathic pain, these data imply that ACT001 could be a potential drug candidate for the treatment of chronic neuropathic pain.